Analysis of Students' Mathematical Communication Ability in the Application of Vygotsky's Theory at High School Level - Muhammad Ishak Sinaga; Bornok Sinaga; Elvis Napitupulu (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study aims to analyze and discover the extent to which students 'mathematical communication skills in the application of Vygotsky's theory, to analyze and find descriptions of students' answer processes through tests of mathematical communication skills, and to analyze and find errors and difficulties of students in developing mathematical communication skills. Data obtained through tests of mathematical communication skills, Vygotsky's Theory questionnaire, student response questionnaires, interview guidelines, and data triangulation. This study uses qualitative data analysis used to analyze data on students' mathematical communication skills and student response questionnaire data through learning in the application of Vygotsky's theory with 5 items of two-variable linear program material in the form of essays in grade XI MIA-2 students of Al Ulum Medan Private High School. Who are given treatment through learning by applying Vygotsky's theory in the odd semester of the 2019/2020 learning year, which has 35 students. Based on the research results, there were 3 students (8.57%) who had a high level of mathematical communication skills; 7 students (20%) have moderate level of mathematical communication skills; 25 students (71.43%) have a low level of mathematical communication skills. After analyzing the student's answer process descriptively, the student's answer process to the mathematical communication test can be concluded that in the first indicator there are 15 students who are able to solve the questions correctly. In the second indicator, there are 8 students who are able to solve the questions correctly. In the third indicator, there are 8 students who are able to solve the questions correctly. In the fourth indicator, there are 4 students who are able to solve the questions correctly. In the fifth indicator, there are 6 students who are able to solve the questions correctly. In the sixth indicator, there are 4 students who are able to solve the questions correctly.